Should we perform in utero MRI on a fetus at increased risk of a brain abnormality if ultrasonography is normal or shows non-specific findings?. Issue 2 (February 2018) - Griffiths, P.D.; Mooney, C.; Bradburn, M.; Jarvis, D.
Abstract : There are a number of reasons why a pregnant woman might be considered to have an increased risk of carrying a fetus with a brain abnormality, but they fall broadly into two groups. First, there may be a relevant family history usually, but not always, when a fetus/child from a previous pregnancy has a developmental brain abnormality and a clinical geneticist judges that there is a risk of recurrence. Second, there may be findings in their current pregnancy that increases the risk of the fetus either having a developmental brain abnormality or accruing acquired brain pathology. Antenatal ultrasonography remains the mainstay of fetal screening and anomaly scanning, but there is now persuasive evidence that in utero magnetic resonance imaging should have an important supporting role. This is important, as more accurate and more certain diagnoses are central to providing parents with accurate information about the likely clinical outcome. In pregnancies at increased risk of brain abnormalities, it is also important to provide the best quality information that the fetal brain is normal to provide reassurance to parents. In this paper, we review the proposition that in utero magnetic resonance imaging should be used in pregnancies at increased risk of brain abnormalities, even if the consultant-led ultrasound examination is normal or showed non-specific findings only.